Peran Resiliensi Terhadap Kecemasan Penyintas Covid-19 - Arnani, Ni Putu Rizky; Husna, Fatiya Halum; Kumala Sari, Citra Ayu (Personifikasi: Jurnal Ilmu Psikologi, 2023)
The covid-19 pandemic that has hit almost all countries in the world has created various new problems in society. The impacts of the pandemic include physical, economic, social and psychological. Covid-19 survivors are individuals who experience psychological impacts. The risk of the covid-19 virus, the uncertainty of conditions, discrimination and social isolation experienced by survivors, are factors that cause anxiety in covid-19 survivors.  The effects of emerging anxiety can be mitigated by resilience. Survivors need resilience to help individuals overcome difficulties during the covid-19 pandemic.  The sampling technique used in this study was non-probability sampling with an incidental sampling design, and a sample size of participant was 138 138 covid-19 survivors. The research instrument used resilience scale and anxiety scale in the form of google forms. The research results show that the F value equal with 52.784, 0.000 smaller than 0.05, which indicates there is significant role of resilience toward anxiety of covid-19 survivors. The role of resilience toward anxiety is 28%, the remaining 72% is influenced by other variables.